1994
DOI: 10.1111/j.1467-8268.1994.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

A Monetarist Model of Inflation: Kenyan Case*

Abstract: A monetarist model of inflation is estimated, incorporating recent developments in time series econometrics. The models compare the performance of both monetary base and a broader monetary aggregate, M3. It is shown that monetary base growth in the inflation model gives relatively stable results. Resum&:On fait l'estimation dlun modele monetariste de l'inflation en y incorporant les evenements de l'economie chronologiquement. Les modeles comparent la performance de la base monetaire et un agregat monetaire plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…To consolidate the gains from the reforms, the central bank of Ghana (BoG) shifted from the use of the exchange rate as a nominal anchor to the use of monetary targets. Under the new regime, quantitative money targets were used as intermediate targets, to achieve ultimate goals such as moderate inflation rate, high output growth rate, and low unemployment rate, among others (see Ndung'u, ; Quartey and Afful‐Mensah, ). Two variants of monetary targeting were operated: directed credit from 1982 to 1991 and open market operation from 1992 to 2006.…”
Section: Introductionmentioning
confidence: 99%
“…To consolidate the gains from the reforms, the central bank of Ghana (BoG) shifted from the use of the exchange rate as a nominal anchor to the use of monetary targets. Under the new regime, quantitative money targets were used as intermediate targets, to achieve ultimate goals such as moderate inflation rate, high output growth rate, and low unemployment rate, among others (see Ndung'u, ; Quartey and Afful‐Mensah, ). Two variants of monetary targeting were operated: directed credit from 1982 to 1991 and open market operation from 1992 to 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Second, technological progress may have changed the relationship between nominal broad money supply and price. Long-run price homogeneity is imposed in line with earlier demand for money studies in Kenya such as Killick and Mwega (1990), Adams (1992), Ndungú (1994), andKisinguh et.al. (2004).…”
Section: Integration and Cointegration Analysismentioning
confidence: 92%
“…This was because that at a higher interest rate, it meant more returns on alternative assets, therefore economic agents will hold less money and more of the alternative assets. Studies such as Ndung'u (1994); Sichei and Kamau (2012) and Kiptui (2014) all reported similar findings.…”
mentioning
confidence: 58%
“…Nonetheless, Laidler (1982) contended that a reasonably quantified income elasticity should be in the range of 0.5 to 1.0. Studies like Ndung'u (1994) and Ndele (1991) also found an income elasticity that was above unity.…”
mentioning
confidence: 89%
See 1 more Smart Citation